Iridium‐Catalyzed Asymmetric Allylic Substitutions with Bulky Amines/Oxidative Double Bond Cleavage – Entry into the Reetz Synthesis of Amino Alcohols. Issue 3 (10th December 2015) - Seehafer, Kai; Malakar, Chandi C.; Bender, Markus; Qu, Jianping; Liang, Chen; Helmchen, Günter
Abstract: Branched allylic amines were prepared by Ir‐catalyzed enantioselective allylic aminations with the bulky N‐nucleophiles HN(Boc)2 and HNBn2 . The products were transformed into N ‐protected amino aldehydes, which were either reduced or coupled diastereoselectively with organometallic compounds to give vicinal amino alcohols. A formal synthesis of the neurokinin receptor antagonist (+)‐L‐733060 was carried out as an application. Abstract : Ir‐catalyzed enantioselective allylic aminations with bulky N‐nucleophiles HN(Boc)2 and HNBn2 gave N ‐protected allylic amines, which were transformed into N ‐protected chiral amino aldehydes. These are useful chiral building blocks as previously demonstrated by Reetz et al. A formal synthesis of the neurokinin receptor antagonist (+)‐L‐733060 was carried out as an application.